Implementation of Indonesian Navy Diplomacy in the Framework of Realizing Indonesia as the World Maritime Axis - Utomo, Budi (IJOSMAS, 2023)
Maritime policy is one of the main focuses of the Indonesian government in realizing Indonesia's vision as the world's maritime axis. The Indonesian Navy's diplomacy plays an important role in supporting this policy, through the implementation of various strategies and efforts to strengthen Indonesia's role in the global maritime world. This research will use a qualitative approach by conducting field surveys, interviews with related parties, and data analysis through literature studies and policy reviews related to the Indonesian Navy L diplomacy. and institutions. The results of the research show that the diplomacy of the TNI-AL consists of a series of steps and activities involving military diplomacy, maritime diplomacy, and cooperation between agencies and institutions. TNI AL Military Diplomacy Is Conducted Through Security Dialogue, Joint Exercises, And Delegation Exchanges With Partner Countries Around The World. The implementation of TNI AL diplomacy has made a significant contribution in realizing the government's maritime policy and Indonesia's vision as the world's maritime axis. Through this diplomacy, the Indonesian Navy L can increase a common understanding of maritime interests, and maintain security stability in Indonesian waters. In addition, TNI AL diplomacy also plays a role in promoting economic and environmental sustainability in the maritime sector